Beta-lactam, aminoglycoside, and quinolone resistance in Escherichia coli strains isolated from shrimps and mussels in the Marmara Sea - Celik, Baran; Ergul, Bahar; Kekec, Ayse Ilgin; Hala, Baris; Maslak, Begum; Sigirci, Belgi Diren; Kahraman, Beren Basaran; Bagcigil, Arzu Funda; Metiner, Kemal; Ak, Seyyal (Veterinarni medicina, 2023)
The purpose of the study was to examine the prevalence of Escherichia coli in shrimps and mussels, and to determine the distribution of β-lactam, aminoglycoside, quinolone, and multi-drug resistance phenotypically and genotypically in E. coli isolates obtained from mussels and shrimps in Istanbul. Faecal samples were collected from mussels (n = 96) and shrimps (n = 96) from the Marmara Sea coastline and fish markets in Istanbul. For the detection of antibiotic susceptibilities, seven antibiotic groups were used. β-lactamase, aminoglycoside, and quinolone genes were also determined. A total of 34 (17.7%, 15 shrimps, and 19 mussels) E. coli were isolated, and 17 (50%) were found to be resistant to one or more antimicrobials. The highest resistance was seen against aminoglycosides with 11 isolates (32.35%), followed by quinolones with 10 isolates (29.41%) and extended-spectrum β-lactamase (ESBL) with 4 isolates (11.76%). Multi-drug resistance was detected in 5 isolates (14.7%) from 3 shrimp and 2 mussel samples. The prevalence of ESBL genes was demonstrated at 3.84% in mussels and shrimp samples. There were no AmpC and carbapenemase-producing genes. These samples harbored blaCTX-M-1 (n = 3) and blaTEM (n = 4). Ten isolates were resistant to aminoglycosides genotypically. Resistance genes detected were strB in 2 isolates, aadA in 5, strB and aadA together in 3, ANT('')-Ia, aphA1 and aphA2 simultaneously in 3, aphA1 in 1, aac(3)-IIa in 1 isolate. aac(6')-Ib-cr gene was detected in only one of 10 phenotypically resistant isolates to quinolones.
Keywords: multiple drug resistance; aquatic animals; ESBL; E. coli